Programmatic outcomes of adolescents in differentiated service delivery models in South Africa - Phumzile M. Shaku; Kate Rees; Barry Mutasa; Christina Maluleke; Steven Mashele; Christine Njuguna (Southern African Journal of Infectious Diseases)
Background: Adolescents living with HIV face barriers that impede adherence and retention. Differentiated service delivery (DSD) models aim to improve retention and viral suppression (VS), but there is limited programmatic evidence from South Africa on DSD outcomes.